Case–control study shows that neonatal pneumococcal meningitis cannot be distinguished from group B Streptococcus cases. (16th June 2017) - Arfi, Alexandra; Cohen, Robert; Varon, Emmanuelle; Béchet, Stéphane; Bonacorsi, Stéphane; Levy, Corinne
Abstract: Aim: Streptococcus pneumoniae ( S. pneumoniae ) is sometimes implicated in neonatal bacterial meningitis. This study described the demographic, clinical and biological features of neonatal S. pneumoniae meningitis and compared pneumococcal and group B streptococcal (GBS) neonatal meningitis. Methods: We conducted a case–control study that compared neonates, aged one to 28 days with S. pneumoniae meningitis or GBS meningitis. Each case with S. pneumoniae was randomly matched to four control patients with GBS by age group and study year. Results: From 2001 to 2013, the national French paediatric network, which comprises 227 paediatric wards, recorded 831 neonatal cases of meningitis. S. pneumoniae (n = 18, 2.2%) was the fifth infection cause after GBS (n = 464, 55.8%), Escherichia coli (n = 232, 27.9%), Neisseria meningitidis (n = 23, 2.8%) and Listeria monocytogenes (n = 20, 2.4%). Neonatal pneumococcal and GBS meningitis did not differ in demographic data or clinical and biological characteristics. All S. pneumoniae strains were fully susceptible to cefotaxime, and we observed a decrease of 13‐valent pneumococcal conjugate vaccine (PCV13) serotypes (88.9%–20.0%) after PCV13 implementation. Conclusion: Clinically and biologically, neonatal pneumococcal meningitis could not be distinguished from GBS cases. A herd effect of PCV13 implementation was suggested by the decrease in the prevalence of vaccine serotypes.